Computational intelligence in business analytics : concepts, methods, and tools for big data applications - Sztandera, Les (FT Press Analytics Ser., 2014)
Use computational intelligence to drive more value from business analytics, overcome real-world uncertainties and complexities, and make better decisions. Drawing on his pioneering experience as an instructor and researcher, Dr. Les Sztandera thoroughly illuminates today's key computational intelligence tools, knowledge, and strategies for analysis, exploration, and knowledge generation. Sztandera demystifies artificial neural networks, genetic algorithms, and fuzzy systems, and guides you through using them to model, discover, and interpret new patterns that can't be found through statistical methods alone. Packed with relevant case studies and examples, this guide demonstrates:Customer segmentation for direct marketingCustomer profiling for relationship managementEfficient mailing campaignsCustomer retentionIdentification of cross-selling opportunitiesCredit score analysisDetection of fraudulent behavior and transactionsHedge fund strategies, and moreSzandera shows how computational intelligence can inform the design and integration of services, architecture, brand identity, and product portfolio across the entire enterprise. He also shows how to complement computational intelligence with visualization, explorative interfaces and advanced reporting, thereby empowering business users and enterprise stakeholders to take full advantage of it. For analytics professionals, managers, and students.